EL IMPACTO DE LAS FUSIONES Y ADQUISICIONES EN LA DISTRIBUCIÓN DEL INGRESO Y EL PIB: AMÉRICA LATINA, 1990-2014 - Alarco Tosoni, Germán (Investigación Económica, 2019)
RESUMEN El artículo presenta los factores explicativos de las fusiones y adquisiciones (F&A), mostrando la evolución, importancia relativa y sectores de destino de esas operaciones en 16 economías de América Latina en el periodo 1990-2014. Con base en un modelo integral, se evalúan los impactos de las F&A en el producto interno bruto (PIB), la vinculación entre el valor de las operaciones de F&A y las ganancias y con ello se determinan los impactos en el consumo privado, la inversión privada y las exportaciones. Se concluye que la elasticidad del PIB respecto al valor de las F&A es negativa en los casos de Chile, Perú y México. Más fusiones reconcentran el ingreso a favor de las ganancias e impactan de forma negativa en el producto. En el resto de las economías de la región estos resultados son ligeramente positivos o inciertos. THE IMPACT OF MERGERS AND ACQUISITIONS ON INCOME DISTRIBUTION AND GROWTH IN LATIN AMERICA, 1990-2014 ABSTRACT The paper reviews the factors accounting for Mergers and Acquisitions (M&As). It then discusses the evolution of M&A trades, their relative importance and the economic sectors that have been influenced by M&As in sixteen Latin-American economies during 1990-2014. An integral model is developed with the aim of assessing both the impact of M&As on Gross Domestic Product (GDP) and the link between the value of M&A transactions and profits so as to determine the effects of profit share changes on private consumption, private investment and exports. The conclusion is reached that the elasticity of GDP with respect to the value of M&As is negative in countries such as Chile, Peru and Mexico. A larger value of M&As tend to redistribute income towards profits and impart a negative impact on output. The impact for other Latin American economies in our sample is either slightly positive or uncertain.